Sol–Gel Synthesis and Photocatalytic Activity of Graphene Oxide/ZnFe2O4-Based Composite Photocatalysts - Tong, Beibei; Shi, Longfei; Liu, Xiaohong (Frontiers in Materials, 2022)
The ZnO (ZO), Fe2O3 (FO) and graphene oxide (GO)/ZO/FO/ZnFe2O4 (ZFO) composite photocatalysts have been synthesized successfully via a simple sol-gel method and low temperature technology. The phase structure and microstructure analysis confirm that the GO/ZO/FO/ZFO magnetic separation photocatalyst is composed of GO, hexagonal ZnO, rhombohedral Fe2O3 and spinel ZnFe2O4 without any other impurities. The GO/ZO/FO/ZFO composite photocatalysts have high visible light optical absorption coefficient and photocatalytic activity for degrading dyes, refractory pollutants and antibiotics. The degradation percentage of methyl orange, tetrabromobisphenol A and oxytetracycline hydrochloride by GO/ZO/FO/ZFO magnetic separation photocatalyst was 98 % for 180 minutes, 99 % for 150 minutes and 85 % for 180 minutes, respectively. The special synthesis path leads to the formation of a special heterojunction between GO, ZnO, Fe2O3 and ZnFe2O4, which does not change the optical band gap value of the main lattice Fe2O3, and enhances the surface defects of GO/ZO/FO/ZFO magnetic separation photocatalyst, resulting in high charge carrier transfer and separation efficiency of the catalyst, and then enhanced the photocatalytic activity of GO/ZO/FO/ZFO magnetic separation photocatalyst.